EFEKTIFITAS KOMPOSISI MEDIA MEDIA SERBUK KAYU, DEDAK PADI DAN TEPUNG JAGUNG TERHADAP PERTUMBUHAN JAMUR TIRAM PUTIH (PLEOROTUS OSTREATUS LINN.) - Abdonia W. Finmeta; Frengky Neolaka; Nardi M. Leo; Nova Y. Loit; Nofita M. Pandie (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The aim of the research was to determine the effect of the composition of wood powder, rice bran and corn flour to grow mushrooms on the growth of white oyster mushrooms (Pleurotus ostreatus Linn.). The research was carried out in February - May 2023 in Noelbaki, Kupang Regency, East Nusa Tenggara. The research was carried out using a completely randomized design (CRD) with 5 treatments and each was repeated 3 times. There were 3 baglogs for each treatment so there were a total of 15 baglogs. The treatments were: Po = 100% wood dust (control), P1 = 85% wood powder : 10% rice bran : 5% corn flour, P2 = 75% wood powder : 15% rice bran : 10% corn flour, P3 = 65% wood dust: 20% rice bran: 15% corn flour, P4 = 55% wood powder: 25% rice bran 20% corn flour. The parameters measured are the initial time of mycelium growth, the time of mycelium fulfillment, the time of fruit body growth, the width of the hood (cm), the length of the stalk (cm), the wet weight of the fruit body (gr) and the dry weight (g). The measurement data were analyzed using variance to determine the effect of the treatment given on the changes observed. From the results of this research it can be concluded that the composition of the mushroom growing media from wood dust, rice bran and corn flour can influence the start of mecelium growth, the time to fulfill the mycelium, the number of fruit bodies, the width of the cap, the dry weight and water content of white oyster mushrooms, the composition of the growing media. The most effective fungus is in treatment 4 with the following ratio of 55% wood dust = 770 grams, 25% rice bran = 350 grams, and 20% corn flour = 280 grams, the greater the amount or mass of rice bran and corn flour, the greater the further accelerates the growth of white oyster mushrooms.